Effects of switching from olanzapine to aripiprazole on the metabolic profiles of patients with schizophrenia and metabolic syndrome: a double-blind, randomized, open-label study - Wani RA (Dove Medical Press, 2015)
Rayees Ahmad Wani, Mansoor Ahmad Dar, Rajesh Kumar Chandel, Yasir Hassan Rather, Inaamul Haq, Arshad Hussain, Altaf Ahmad MallaDepartment of Psychiatry, Government Medical College, Srinagar, Jammu and Kashmir, IndiaBackground: Patients with schizophrenia suffer high rates of metabolic derangements on some antipsychotic medications that predispose them to cardiovascular diseases. Keeping this fact in mind, we planned this open-label study to see the effect on various metabolic parameters after switching stable schizophrenia subjects, who had developed metabolic syndrome on olanzapine, to aripiprazole.Methods: Sixty-two patients with schizophrenia who were stable on olanzapine and were fulfilling modified National Cholesterol Education Program (NCEP) Adult Treatment Panel III (ATP-III) criteria for the presence of metabolic syndrome were enrolled on the study. Patients were randomly assigned either to switch to aripiprazole or to stay on olanzapine, on a 1:1 basis. Cross-tapering over a period of 1 month was done while switching patients to aripiprazole. Laboratory assessment for metabolic parameters was done at baseline, 8 weeks, and 24 weeks after enrollment; efficacy assessment was done using the Positive and Negative Syndrome Scale (PANSS) at baseline and 24 weeks, the Clinical Global Impressions severity subscale (CGI-S) at baseline, and the Clinical Global Impressions improvement subscale (CGI-I) at 24 weeks.Results: All parameters of metabolic syndrome (waist circumference, blood pressure, triglyceride level, fasting blood glucose, and high-density lipoprotein cholesterol) kept deteriorating in the stay group, compared with a continuous improvement in the switch group over time. At the end of the study, 26 patients (100%) from the stay group and 15 patients (42.8%) from switch group met the modified NCEP ATP-III criteria for presence of metabolic syndrome (P<0.001). There were no statistically significant differences between groups in psychopathology changes as measured by the PANSS total score and CGI-I scores.Conclusion: Clinically stable patients with schizophrenia who are taking olanzapine and who have evidence of metabolic syndrome can be successfully switched to aripiprazole, with improvement in various parameters of metabolic syndrome and without any significant change in efficacy measures.Keywords: metabolic syndrome, olanzapine, aripiprazole, schizophrenia, switching